Electric field development in positive and negative streamers on dielectric surface. (8th October 2021) - Jánský, J; Bessiéres, D; Brandenburg, R; Paillol, J; Hoder, T
Abstract: Multiplication of primary electrons at a dielectrics/gas interface exposed to an external electric field leads to the formation of ultra-fast contracted ionisation waves called surface streamers with high local electric field in their microscopic heads. We study this phenomenon in coplanar barrier discharge in atmospheric pressure air where streamers of both polarities are generated simultaneously. The electric field strength development in the discharge is determined experimentally using time-correlated single photon counting enhanced optical emission spectroscopy with high spatiotemporal resolution. We show that very high values of the electric field of even above 1200 Td (approx. 300 kV cm −1 ) can be a physical reality for positive streamer directly at the dielectric surface. The peak value for negative streamer lies under 200 kV cm −1 . In parallel, a two-dimensional fluid model describes the rapidly changing electric field and the spatiotemporal discharge dynamics in good agreement with the experimental results. We also present the theoretical results of spatiotemporal development of electron density and of charge transfer to the dielectric surface via a collapsing sheath as the discharge structure decays within a very few nanoseconds.